Evaluation of Orthodontic Treatment Need and Its Correlation with the Perception, Awareness and Satisfaction of Personal Dental Appearance among Dental Students - Malik, Vikas; Grover, Seema; Sidhu, Maninder Singh; Yadav, Puneet; Chaudhary, Priti (Journal of Orofacial Research, 2013)
Introduction: Facial esthetics as well as dental health improvements is the main concern of orthodontic treatment. Dentofacial appearance that deviates from normal may have anegative impact on social, physiological and psychological functions. But individual’s attitude to its malocclusion is an important factor in determining treatment need.Objectives: The study was conducted to assess the perception of malocclusion and need of orthodontic treatment among dental students using index of orthodontic treatment need (IOTN). Also self-awareness and level of satisfaction of personal dental appearance were analyzed. Materials and methods: Sample of 300 dental students was selected, their alginate impressions were poured, and study casts were prepared. IOTN was used to find out the impact of malocclusion on individual’s dental health and psychological well being. A questionnaire was prepared consisting of part 1, self-awareness and part 2, satisfaction and attitudes. Each part consisted of series of questions with alternative answers. Eachselected subject was given this questionnaire for self-evaluation and self-perception of occlusion and facial appearance.  Results: Majority of dental students were observed in grades Iand II of IOTN indicating no or minimal treatment need. The students were aware that malocclusion, orthodontic treatment and facial esthetics are the important factors for self-image and self-esteem.